The Legal Problems and Guidelines Related to the Legality of Carrying Firearms by Police Officers - Kowit, Siporn (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The purposes of this research were to study 1) to study of the legal problems, criteria, measures and guidelines for the control of carrying firearms by police officers; and 2) to get of the offer appropriate guidelines for the legality of carrying firearms by police officers. A qualitative method was used for data analysis including document research, in-depth interviews 17 key informant and content analysis. The research findings show that: 1) Police officers are representatives of the state who protect the rights of the people; if they do not perform their duties for the benefit of the people, leave the official building or are off duty, there is no legal basis or justification for carrying firearms 2) Legislation should clearly define the scope of police officers' powers and responsibilities and the carrying of firearms is not required unless there is a direct responsibility to investigate, prevent, or combat crime and protect the public. The scope of authority and protection afforded by the carrying of firearms is unnecessary because police officers are not required to carry firearms as part of their official duties, and 3) The guidelines for carrying a police officer's firearm should include the following: installation of a body camera to record audio and video while on duty; requirement of regular firearms training; verification of the readiness of each police firearm; review of work history and conduct by a supervisor subject to hierarchical oversight; and exercise of emotional control. If a police officer does not meet these qualifications, they may not carry firearms. The risk of using a firearm and causing harm depends on the individual's suitability.